A Risk Management Approach for the Pre-Series Logistics in Production Ramp-Up - Patrick Filla; Katja Klingebiel (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Due to continuing derivatisation and increasing customer requirements, automotive development projects constantly become more complex. With a shortening time-to-market, the critical ramp-up phase of a new or updated automobile is susceptible to a variety of disruptions. As the project duration is naturally restricted, a high number of unscheduled ad-hoc resources are regularly installed to achieve the previously set qualitative targets within the given time limits. For early risk mitigation, current approaches in research and industry focus on the measurement of either technical product degrees or process maturity degrees in the development process. Nevertheless, it is clearly understood, that pre-series logistics bridge both viewpoints and thus still hold significant potential to reduce project risks. Consequentially, this paper presents a methodology that assesses the risk of process-wise and quality-wise delays. After discussing the specific risk profiles within logistics processes in the automotive ramp-up phase, the application of purpose-designed product maturity degree indicators and structured knowledge from historical projects is illustrated. The developed approach enables to identify critical processes in the production readiness process. The paper concludes with a summary and an outlook on further research.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; ramp-up; pre-series logistics; risk management; production development